2017
DOI: 10.1108/he-05-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Nordic children’s conceptualizations of healthy eating in relation to school lunch

Abstract: Purpose Pupils’ perspective should be better taken into account when developing nutrition education at school. The purpose of this paper is to explore Nordic children’s perspectives on the healthiness of meals in the context of school lunches. Design/methodology/approach In total, 78 focus group discussions were conducted with 10-11-year-old girls and boys (n=457) from schools in Finland, Iceland, Norway and Sweden, which were participating in the Nordic school meal project ProMeal during the school year 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This may include the music they listen to, the Internet sites they visit, what is trendy at the moment, which series or movies are popular, and so on (Efken, 2002). Kuchah and Pinter (2012), Lund, Helgeland, and Kovac (2016), and Berggren et al (2017) spent time with the participants doing confidence-building activities such as playing sports or games or just participating in their daily life in kindergarten prior to the interviews.…”
Section: Role Of the Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may include the music they listen to, the Internet sites they visit, what is trendy at the moment, which series or movies are popular, and so on (Efken, 2002). Kuchah and Pinter (2012), Lund, Helgeland, and Kovac (2016), and Berggren et al (2017) spent time with the participants doing confidence-building activities such as playing sports or games or just participating in their daily life in kindergarten prior to the interviews.…”
Section: Role Of the Moderatorsmentioning
confidence: 99%
“…Moderators of focus groups with children should integrate seeing, touching, and moving about. Such activities may include to ask children to list things, rate items, sort or draw pictures, create mind maps or flowcharts, dream, or use their imagination (Berggren et al, 2017;Cammisa et al, 2011;C. D. Clark, 2011;Davies & Robinson, 2010;Krueger & Casey, 2009;Moffat et al, 2009).…”
mentioning
confidence: 99%
“…(Edward, negative frame story) The images and emotions described in relation to food and eating encompassed children being served their favorite dish and pancakes, taco, pizza and hamburgers were frequently mentioned, most often in a positive sense. This is interesting since pupils from the same study population, when being interviewed in focus groups about what they felt was important regarding school lunch (Berggren et al 2017), had a clear emphasis on the healthiness of the meal where those dishes were usually labeled as bad and unhealthy foodacceptable only if eaten seldom. In that study, the food and eating-related emotions that emerged in the discussions were only in relation to unhealthy eatingsuch as feelings of joy and disgust.…”
Section: Food and Eatingmentioning
confidence: 99%
“…While all of the thirty-one articles reviewed for this paper focused on learners in compulsory education, they covered a wide range of topics within education in a variety of countries. These included gender and bullying in schools in England (Newman et al, 2006), inclusion of learners with special educational needs and disabilities in UK, Zambia and Indonesia (Kaplan et al, 2007), the school experiences of Black middle-class male youth in high school in usa (Allen, 2012), the views of learners in Nordic countries on healthy and unhealthy eating (Berggren et al, 2017), transition of learners from primary to secondary schools in Bangladesh (Shohel, 2012), the understandings of inclusion held by migrant learners in schools in England (Hanna, 2018) and friendship and meaning in young people's lives in Australia (O'Rourke et al, 2019). The themes explored are necessarily selective and not intended to be exhaustive.…”
Section: Research Review Themesmentioning
confidence: 99%
“…Mitchell (2008), in her extensive research in South Africa, suggested that using such methods forms part of a researcher's social responsibility to encourage participation in educational research of a variety of groups. Several studies went further to suggest that photographic methods were specifically child-friendly (e.g., Berggren et al, 2017;Sutherland & Young, 2014;Cook & Hess, 2007). However, a question does arise as to the particular ways in which participants might be participating or not participating -such as whether lack of enthusiasm for taking photographs might represent a withdrawal of consent (Barker & Smith, 2012) -as well as whether that creates a false sense of agency to effect change (Allen, 2009).…”
Section: Why Photography Is Used: Representation Participation and Ementioning
confidence: 99%